Aerobic Exercise Affects T-wave Alternans and Heart Rate Variability in Postmenopausal Women - Shen, T.-W.; Wen, H.-J. (International Journal of Sports Medicine, 2013)
The purpose of this study was to investigate the effects of a 10-week high-intermediate exercise intervention on heart rate variability/microscopic T-wave alternans (HRV/MTWA) in healthy postmenopausal women (PMW). 62 healthy PMW were recruited and randomly divided into an exercise group (EG, n=32) or a control group (CG, n=30). The EG attended a progressively high-intermediate intensity (75–85% heart rate reserve, HRR) group-based step aerobic exercise program for 10 weeks, whereas the CG did not receive any intervention. HRV/MTWA, blood chemistry and physical function-related indices were measured before and within 24 h following the 10-week exercise program. Following a 10-week exercise intervention, the EG had significant mean decreases in SDNN (22.4%), CV (21.4%), NN50 (72.6%), LF (ms2; 55.8%), HF (ms2; 39.9%), LF (n.u.; 11.2%), and LF/HF (34.5%). The EG showed a significant increase in HF (n.u.; 40.0%) and CAV (44.4%), whereas there was no significant finding in the CG. The coupling effect of MTWA and HRV after intervention suggests that exercise intervention potentially affects regulation changes of the autonomic nervous system and cardiovascular condition synchronically in PMW. The rebound effect of biomarkers has proven to be a considerable factor on HRV/MTWA measurements.
Keywords: short-term intervention; cardiac index; sudden cardiac death; group-based step aerobic exercise